The Rise of New Media and Product Promotion: Exploring the Potential of Online Media in Advertising the Services Provided by Major Telecommunications Service Providers in India - Trehan, Kulveen (Indian Journal of Marketing, 2012)
The paper attempts to gain insight into the use and nature of online media in telecommunication advertising. The very nature of the medium and the technological services under the study makes it an interesting area to explore. If on one hand, the present study deals with online media - the first segment of new media communication, the industry under exploration is cellular services with an aim to increase the use of applications on mobile phones - the second major component of new media. To study the two in combination provides an opportunity to find out the extent of the rise of new media as a marketing communication toolkit. Online advertising content is critically examined qualitatively to arrive at applicable constructs.